Sustainable application of waste gangue mortar in coal mine tunnel support - Yang Liu; Luming Zhu; Xijun Liang; Jintao He; Guiwen Suo; Haoran Wu; Bin Li; Zimu Wang (Scientific Reports)
Abstract With the increase in coal mining depths, soft and fractured roadway surrounding rocks require grouting and a sprayed protective layer for maintenance. Simultaneously, extensive accumulation of coal gangue causes diverse environmental issues. To enhance on-site coal gangue utilization, this study replaced river sand and cement with coal gangue to develop a novel cement-based mortar for supporting coal mine roadways. The study examined how apparent density, compressive strength, flexural strength, and fiber reinforcement affect performance, while investigating the hydration reaction mechanism. The results show that compared with ordinary mortar, the apparent density and compressive strength of coal gangue-basalt fiber cementitious mortar are reduced, but its flexural strength is improved. Furthermore, a constitutive model for coal gangue-basalt fiber cement-based mortar under compression was formulated. The model comprehensively assessed the compressive strength of specimens and determined correlation coefficients for the rising and falling sections of the stress-strain curve. Micro-aggregates enhance the internal skeleton density in coal gangue-basalt fiber cement-based mortar.